2005
DOI: 10.2754/avb200574010111
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron and Granisetron in Prophylaxis of Nausea and Emesis Inducedby Cisplatin in Dogs

Abstract: Topal A., M. Kaya, N. Gül: Ondansetron and Granisetron in the Prophylaxis of Nausea and Emesis Induced by Cisplatin in Dogs. Acta Vet. Brno 2005, 74: 111-116. In the present study, the effects of 5-HT3 receptor antagonist granisetron and ondansetron on the acute phase of cisplatin-induced nausea and emesis were analyzed in dogs.Fifteen healty dogs were used in this study. Cisplatin was administrated to all dogs to induce nausea and vomiting. All dogs that received cisplatin (3 mg/kg IV) were observed contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Cisplatin is one of the chemotherapeutic agents which has been used in the clinical management of various carcinomas like ovarian, testicular, head and neck carcinomas (Muggia, 2009) having one of the severe limiting side effect of nausea and vomiting (Topal et al, 2005). The vomiting caused by chemotherapeutic drugs is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin is one of the chemotherapeutic agents which has been used in the clinical management of various carcinomas like ovarian, testicular, head and neck carcinomas (Muggia, 2009) having one of the severe limiting side effect of nausea and vomiting (Topal et al, 2005). The vomiting caused by chemotherapeutic drugs is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from its useful broad spectrum anti-cancer activity, it has a lot of adverse reactions as well including oxidative stress (Sodhi and Gupta, 1986), lipid peroxidation (Sugihara et al, 1987), hypocalcemia, hypomagnesia (Hodgkinson et al, 2006;Lajer and Daugaard, 1999;Martin et al, 1992), nausea and vomiting (Qiu-hai et al, 2010), ototoxicity (Rybak et al, 2007), stomach distention and nephrotoxicity (Aggarwal et al, 1994). Nausea and vomiting (Glaus et al, 2004;Topal et al, 2005) are the major dose limiting adverse reactions which leads to *Corresponding author. E-mail: Ihsanmrd@upesh.edu.pk.…”
Section: Introductionmentioning
confidence: 99%
“…Ondansetron already is used in veterinary medicine for the treatment of nausea after chemotherapy. 8,34 Studies showed a decrease of the nausea score, as well as in the frequency of vomiting. These results have been observed in other experimental studies, such as in dogs with renal disease or when used against preoperative nausea.…”
Section: Discussionmentioning
confidence: 96%
“…Ondansetron already is used in veterinary medicine for the treatment of nausea after chemotherapy 8,34 . Studies showed a decrease of the nausea score, as well as in the frequency of vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…ondansetron) led to improved prevention of acute emesis but delayed vomiting was still frequently seen (Sagrada and others 1991 [1b]). A small experimental trial of cisplatin‐induced emesis in dogs showed that pre‐treatment with both ondansetron and granisetron could significantly inhibit vomiting (Topal and others 2005 [3b]). Recently, the NK‐1 antagonist, maropitant, has proven its efficacy in the prevention of emesis after treatment with cisplatin in the clinic (De La Puente‐Redondo and others 2007b [1b], Vail and others 2007 [1b]).…”
Section: Prevention and Treatment Of Vomiting In The Dogmentioning
confidence: 99%